(untitled) (Perspectivas de las Ciencias Económicas y Jurídicas, 2017)
Currently, a paradigm of clinical management of intersexuality, characterized by performing genital reconstruction surgeries in the first years of life, and continuous hormonal therapies, as well as the patient’s subsequent lack of knowledge about their intersexual condition through of concealment or modification of their clinical history and the imposition of family secrecy. Despite the significant advances of the Gender Identity Law 26,743 regarding gender diversity, it did not specifically contemplate the situation of medical interventions on intersex births. This omission will be analyzed as part of a deeper process of cultural invisibility of the construction of bodies and identities, which seeks to obtain lives anchored in a homogenous, decipherable, readable and desirable corporality, not subversive and not shameful. On the other hand, it is part of a concrete effort to express the need to build an alternative humanism that allows the development of protocols that do not pathologize intersexuality and provide ways of action that facilitate a change in the concept of the human and the social, to guarantee the dignity of people who have no place in the dichotomous schemes of sexual identity